2014
DOI: 10.1109/jstars.2014.2342291
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Area Index Estimation Using Vegetation Indices Derived From Airborne Hyperspectral Images in Winter Wheat

Abstract: Continuous monitoring leaf area index (LAI) of field crops in a growing season has a great challenge. The development of remote sensing technology provides a good tool for timely mapping LAI regionally. In this study, hyperspectral reflectance data (405-835 nm) obtained from an airborne hyperspectral imager (Pushbroom Hyperspectral Imager) were used to model LAI of winter wheat canopy in the 2002 crop growing season. LAI was modeled based on its semi-empirical relationships with six vegetation indices (VIs), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Many previous studies have successfully estimated crop biomass using airborne hyperspectral data [1,17]. However, our study found that VIs derived from CASI data had limited capability in estimating the biomass of maize.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Many previous studies have successfully estimated crop biomass using airborne hyperspectral data [1,17]. However, our study found that VIs derived from CASI data had limited capability in estimating the biomass of maize.…”
Section: Discussionmentioning
confidence: 65%
“…Many previous studies have investigated a list of VIs derived from hyperspectral data for crop biomass estimation [1,7,17,43]. Based on the findings of these studies, six VIs were selected to estimate biomass of maize in this study (Table 2): Simple Ratio Vegetation Index (SR) [44], Normalized Difference Vegetation Index (NDVI) [45], Modified Simple Ratio Index (MSR) [24], Modified Soil-Adjusted Vegetation Index (MSAVI) [46], Red Edge NDVI (ReNDVI) [47] and Red Edge Modified Simple Ratio Index (ReMSR) [15].…”
Section: Deriving Metrics From Hyperspectral Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the PHI images were denoised with the Savitzky-Golay method to further improve the image quality (Xie et al, 2014). The denoised spectrum acquired with PHI sensor on April 18, May 17 and May 31 were presented in Fig.…”
Section: Airborne Campaignsmentioning
confidence: 99%